Diverticulitis of Cecum Mimicking Plastron Appendicitis: A Diagnostic and Therapeutic Dilemma. Issue 4 (October 2013) - Arikanoglu, Zulfu; Taskesen, Fatih; Kapan, Murat; Gümüş, Hatice; Tacyildiz, Ibrahim Halil
No abstract available